2014
DOI: 10.1002/eji.201444972
|View full text |Cite
|
Sign up to set email alerts
|

The role of the microbiota in inflammation, carcinogenesis, and cancer therapy

Abstract: Commensal microorganisms colonize barrier surfaces of all multicellular organisms, including those of humans. For more than 500 million years, commensal microorganisms and their hosts have coevolved and adapted to each other. As a result, the commensal microbiota affects many immune and nonimmune functions of their hosts, and de facto the two together comprise one metaorganism. The commensal microbiota communicates with the host via biologically active molecules. Recently, it has been reported that microbial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
189
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(202 citation statements)
references
References 188 publications
(284 reference statements)
2
189
0
11
Order By: Relevance
“…Interestingly, the same LNK polymorphism that is associated with hypertension is also associated with celiac disease. A recent study by Katayama et al [18] demonstrated that LNK deficient mice had intestinal pathology resembling human celiac disease that was associated with enhanced IFNγ producing CD8 + T cells in the spleen, mesenteric lymph nodes, and intestinal lamina propria.…”
Section: Lnk/sh2b3 Regulates Blood Pressure and Ifnγ Productionmentioning
confidence: 99%
“…Interestingly, the same LNK polymorphism that is associated with hypertension is also associated with celiac disease. A recent study by Katayama et al [18] demonstrated that LNK deficient mice had intestinal pathology resembling human celiac disease that was associated with enhanced IFNγ producing CD8 + T cells in the spleen, mesenteric lymph nodes, and intestinal lamina propria.…”
Section: Lnk/sh2b3 Regulates Blood Pressure and Ifnγ Productionmentioning
confidence: 99%
“…Recently, the gut microbiome has been shown to play a crucial role in health, as well as in diseases such as obesity,16 inflammatory bowel disease,17, 18 diabetes,19, 20 non‐alcoholic fatty liver disease,21, 22, 23 and several types of cancers 24, 25. Experimental evidence indicates that the human intestinal microbiome can influence tumor development and progression in the gastrointestinal tract by damaging DNA, activating oncogenic signaling pathways, producing tumor‐promoting metabolites, and suppressing the antitumor immune response 7, 25, 26, 27, 28, 29. As the gastrointestinal microbiota can be modified through the rational deployment of antibiotics, probiotics, and prebiotics,30, 31, 32 a better understanding of the relationship between human cancer and the microbiome may have clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…7, 8, 14 The mechanisms by which these disorders are linked to disruptions in the microbiome are currently under investigation, but it has been suggested, for example, that the microbes colonizing the epithelial barrier surfaces interact with the host either directly or through released products, regulating local inflammation and immunity. 15, 16 The host immune system and the gut microbiome appear to have a physiological interaction. This is central to preventing tissue-damaging inflammatory responses directed against commensals (such as different species of Lactobacilli and Proteobacteria in the small intestine, Clostridia and Bacteroides in the colon), while avoiding infection by pathogens (e.g., Salmonella and Shigella spp.)…”
Section: Human Microbiome In Diseasesmentioning
confidence: 99%